Hydrogen Sulfide Inhibits Cigarette Smoke-Induced Endoplasmic Reticulum Stress and Apoptosis in Bronchial Epithelial Cells - Lin, Fan; Liao, Chengcheng; Sun, Yun; Zhang, Jinsheng; Lu, Weiwei; Bai, Yu; Liao, Yixuan; Li, Minxia; Ni, Xianqiang; Hou, Yuelong; Qi, Yongfen; Chen, Yahong (Frontiers in Pharmacology, 2017)
Background: Apoptosis of lung structural cells contributes to the process of lung damage and remodeling in chronic obstructive pulmonary disease (COPD). Our previous studies demonstrated that exogenous hydrogen sulfide (H2S) can reduce the lung tissue pathology score, anti-inflammation and anti-oxidation effects in COPD, but the effect of H2S in regulating cigarette smoke (CS) induced bronchial epithelial cell apoptosis and the underlying mechanisms are not clear. Objectives: To investigate the effect of H2S on CS induced endoplasmic reticulum stress (ERS) and bronchial epithelial cell apoptosis. Methods: Male Sprague–Dawley rats randomly divided into four groups for treatment: control, CS, NaHS + CS, and propargylglycine (PPG) + CS. The rats in the CS group were exposed to CS generated from 20 commercial unfiltered cigarettes for 4 h/day, 7 days/week for 4 months. Since the beginning of the third month, freshly prepared NaHS (14 μmol/kg) and PPG (37.5 mg/kg) were intraperitoneally administered 30 min before CS-exposure in the NaHS and PPG groups. 16HBE cells were pretreated with Taurine (10 mM), 5 mmol/L 4-phenylbutyric acid (4-PBA) or NaHS (100, 200, and 400 μM) for 30 min, and then cells were exposed to 40 μmol/L nicotine for 72 h. ERS markers (GRP94, GRP78) and ERS-mediated apoptosis markers 4-C/EBP homologous protein (CHOP), caspase-3 and caspase-12 were assessed in rat lung tissues and human bronchial epithelial cells. The apoptotic bronchial epithelial cells were detected by Hoechst staining in vitro and TUNEL staining in vivo. Results: In CS exposed rats, peritoneal injection of NaHS significantly inhibited CS induced overexpression ERS-mediated apoptosis markers and upregulation of apoptotic rate in rat lungs, and inhibiting the endogenous H2S production by peritoneal injection of PPG exacerbated these effects. In the nicotine-exposed bronchial epithelial cells, appropriate concentration of NaHS and ERS inhibitors taurine and 4-PBA inhibited nicotine-induced upregulation of apoptotic rate and overexpression of ERS-mediated apoptosis markers. Conclusion: H2S inhibited lung tissue damage by attenuating CS induced ERS in rat lung and exogenous H2S attenuated nicotine induced ERS-mediated apoptosis in bronchial epithelial cells.